The Influence of Absorber Properties on Operating Parameters and Electricity Generation in the Solar Chimney with a Vertical Collector - Sylwia Berdowska (Energies)
The paper presents an analysis of the operating parameters of a solar chimney with a non-selective and selective absorbers. The analyzed system consisted of a rectangular vertical collector integrated with a chimney. The collector surface was 30 m2, while the installation was 80 m high. The calculations were performed for the climatic conditions in Katowice, Poland. The work included an analysis of parameters such as air temperature increase and its velocity and mass flow in the solar chimney system. The cumulative amounts of electricity that can be obtained in each month of the year were shown. A comparison of electricity generation in the installation with an absorber covered with a non-selective coating and selective coatings was made. The installation with an absorber with an absorption coefficient of 0.95 and an emission coefficient of 0.05 allowed for the generation of the largest amount of electricity during the year.